2020
DOI: 10.1007/s11103-020-00973-5
|View full text |Cite
|
Sign up to set email alerts
|

Precise evaluation of tissue culture-induced variation during optimisation of in vitro regeneration regime in barley

Abstract: Key message The Taguchi method and metAFLP analysis were used to optimise barley regenerants towards maximum andminimum levels of tissue culture-induced variation. The subtle effects of symmetric and asymmetric methylationchanges in regenerants were identified. Abstract Plant tissue cultures (PTCs) provide researchers with unique materials that accelerate the development of new breeding cultivars and facilitate studies on off-type regenerants. The emerging variability of regenerants derived from PTCs may have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 64 publications
5
52
2
Order By: Relevance
“…Genotyping of the isolated DNAs using the metAFLP approach allowed the identification of 407 markers shared by the donor plant and regenerants [25]. Quantitative metAFLP characteristics of the DNAs are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotyping of the isolated DNAs using the metAFLP approach allowed the identification of 407 markers shared by the donor plant and regenerants [25]. Quantitative metAFLP characteristics of the DNAs are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, abiotic stresses such as cold and drought are responsible for changes in DNA methylation patterns [22]. Additionally, studies on plant responses to in vitro tissue culture-induced stress show that tissue culture conditions promote changes in stress-induced DNA methylation and/or demethylation patterns [23][24][25][26][27]. Machczyńska and colleagues reported a relatively high level of DNA sequence variation between the donor plant and its regenerants [28].…”
Section: Introductionmentioning
confidence: 99%
“…The approach is being world-wide used, but a growing number of data clearly shows that plant regeneration via anther culture is affected by an in vitro tissue culture-induced variation (TCIV) [ 44 , 45 , 46 , 47 ] that could be transmitted to a progeny [ 48 ]. Among others, the TCIV is due to changes in the DNA methylation patterns that are under either genetic or epigenetic control [ 49 ]. As plant regeneration requires cell reprogramming [ 18 ] involving DNA methylation pattern change, it is of value to understand whether ingredients present in the in vitro medium participating in many cellular biochemical pathways [ 17 , 50 , 51 ] and other factors such as time of in vitro cultures may affect methylation changes and the number of the regenerated green plants that may be limited by the presence of albinos [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The approach is being world-wide used, but a growing number of data clearly shows that plant regeneration via anther culture is affected by an in vitro TCIV [54][55][56][57] that could be transmitted to a progeny [58]. Among others, the TCIV is due to changes in the DNA methylation patterns affecting distinct methylation contexts (symmetric and asymmetric) that are under either genetic or epigenetic control [44]. As plant regeneration requires cell reprogramming [1] involving DNA methylation pattern changes, it is of value to understand whether ingredients present in the in vitro medium and other factors such as the time of in vitro cultures may affect methylation changes and the number of the regenerated green plants that may be limited by the presence of albinos [59].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated that manipulating Cu 2+ , Ag + ion concentration one may optimize in vitro anther cultures of barley towards the increased number of green plants [43]. We have also shown that under varying conditions of Cu 2+ , Ag + , and time (T) differences in DNA methylation of the symmetric and asymmetric context may appear [44]. According to that results, the role of the time seems to be negligible, whereas the others [45] indicated that the longevity of in vitro tissue cultures might influence DNA methylation pattern [46] or even sequence changes [47].…”
Section: Introductionmentioning
confidence: 98%